Я - вор в законе. Облава - Сухов Евгений Евгеньевич (Я - вор в законе, 2003)
Экземпляры: аб. ЦБ (20190912) / Инвентарный номер: 7346 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: С91 / ББК: 84(2Рос=Рус)6